STABILITY INDICATING HPTLC METHOD DEVELOPMENT AND VALIDATION FOR COMBINED DOSAGE FORM OF TOLPERISONE HYDROCHLORIDE AND DICLOFENAC SODIUM - Bavaliya, Paresh; Kalkani, Vijay; Kashyap, Raval (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
A simple HPTLC method has been developed and subsequently validated for tablet dosage form. The method employed TLC aluminum plates precoated with silica gel 60F254 as the stationary phase. The solvent system consist of Methanol: Toluene: Ethyl Acetate (2.5:7:0.5 v/v/v) and saturation time was 25 min.This system was found to give compact spots for diclofenac sodium (Rf =0.7±) and tolperisone hydrochloride (Rf 0.5).Analysis of tolperisone hydrochloride, diclofenac sodium was carried out at 275nm. Linearity of diclofenac sodium and tolperisone hydrochloride was found to be y = 5.3727x + 4514.2, R2=0.998, y = 9.376x + 2635.6, R2=0.995 respectively in concentration range of 300-1500 µg/bandand 100-300 µg/band. %Assay of tolperisone hydrochloride and diclofenac sodium was found to be 99.16%w/v and 99.60 %w/v.Results of all other experiments for method validation were found within the specified criteria of ICH guideline.